The Impact of Breakdown in Filiation: The Instance of Children Exiled From Reunion Island to Mainland France Between 1962 and 1984 - Feldman, Marion; Mansouri, Malika (Frontiers in Psychology, 2021)
The aim of this article was to show the consequences of breakdowns in filiation among people born between 1950 and 1970 on Reunion Island, who experienced particular traumas during their childhood. The research participants were among the 2 015 children exiled from Reunion Island to mainland France between 1962 and 1984, as part of a political project. Most of them we adopted, others were placed in foster families, foster homes or farms. The forced exile was orchestrated by the French social services in charge of child protection (DDASS). Structured interviews were conducted with thirteen people exiled when they were between 2 and 15 years old. The interviews were transcribed and then analysed. The results show that these children were exposed to abuse in their filiation through a series of traumas. For them, this abuse is still active today, as the French government has not yet acknowledged the suffering of these children. The participants displayed numerous psychic disorders linked to their abandonment. They are still experiencing difficulties in assuming their identity, and these difficulties are transmitted to the next generation. Analysis of the impact of these filiation breakdowns leads the present researchers to suggest a specific clinical setting, based on a focus group, in other words a group therapy aiming to generate a group narrative process.